2016
DOI: 10.1177/0271678x16669512
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal assessment of neurovascular coupling during cerebral ischaemia and reperfusion using remote middle cerebral artery occlusion

Abstract: Hyperacute changes in cerebral blood flow during cerebral ischaemia and reperfusion are important determinants of injury. Cerebral blood flow is regulated by neurovascular coupling, and disruption of neurovascular coupling contributes to brain plasticity and repair problems. However, it is unknown how neurovascular coupling is affected hyperacutely during cerebral ischaemia and reperfusion. We have developed a remote middle cerebral artery occlusion model in the rat, which enables multi-modal assessment of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Similarly, Brad et al . monitored that brain activity and the time-dependent neurophysiological and hemodynamic response during the cerebral ischemia and reperfusion process [ 10 ]. Damage to the BBB is one of the consequences of stroke with the greatest impact.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Brad et al . monitored that brain activity and the time-dependent neurophysiological and hemodynamic response during the cerebral ischemia and reperfusion process [ 10 ]. Damage to the BBB is one of the consequences of stroke with the greatest impact.…”
Section: Introductionmentioning
confidence: 99%
“…Sullender presented a dual‐modality imaging system to simultaneously map cortical blood flow and oxygen tension for studying the pathological features in the acute photothrombotic stroke [44]. Buchan used a multimodal approach to assess hyperacute changes in cerebral blood flow during cerebral ischemia and reperfusion by combining LSCI and microelectrode techniques, offering unique insights into the pathophysiology of hyperacute ischemia [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that hyperemia following stroke can actually result in low tissue oxygenation due to impaired capillary transit time heterogeneity, 44 along with the increased risk of oxidative injury during hyperperfusion post-stroke 45 and a dysfunction of neurovascular coupling. 13 This may represent an ischemia-reperfusion injury paradigm in the brain that has recently been proposed but not confirmed in human subjects due to the paucity of appropriate blood flow imaging techniques able to detect these changes. 6,7 Interestingly, another study showed that hyperperfusion within one day post-MCAO was associated with smaller lesions but sustained hyperperfusion at four days post-MCAO was associated with infarct growth.…”
Section: Discussionmentioning
confidence: 99%
“…The use of animal models of stroke allows continuous measurement of blood flow with greater spatial and temporal resolution than the techniques used in humans. Techniques such as Laser Doppler Flowmetry (LDF), Laser Speckle Contrast Imaging, 14 C-iodoantipyrine autoradiography and hydrogen clearance [12][13][14][15] but also optical techniques such as optical coherence tomography, photoacoustic microscopy, optical imaging spectroscopy and two-photon microscopy 16 have been used in animal studies. These techniques require invasive surgical (i.e.…”
Section: Introductionmentioning
confidence: 99%